2011
DOI: 10.1007/s00271-011-0303-3
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of 1D surface and 2D subsurface water flow and nitrate transport in alternate and conventional furrow fertigation

Abstract: Increasing water and fertilizer productivity stands as a relevant challenge for sustainable agriculture. Alternate furrow irrigation and surface fertigation have long been identified as water and fertilizer conserving techniques in agricultural lands. The objective of this study was to simulate water flow and fertilizer transport in the soil surface and in the soil profile for variable and fixed alternate furrow fertigation and for conventional furrow fertigation. An experimental data set was used to calibrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 28 publications
(23 reference statements)
2
33
0
Order By: Relevance
“…For instance, Ebrahimian et al (2013a) (Simunek et al, 1999): [17] where D w is the molecular diffusion coefficient in free water [L 2 T -1 ]; τ w is the tortuosity factor (dimensionless); ‰ ij is the Kronecker delta function (δ ij = 1 if i = j, and…”
Section: Subsurface Solute Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Ebrahimian et al (2013a) (Simunek et al, 1999): [17] where D w is the molecular diffusion coefficient in free water [L 2 T -1 ]; τ w is the tortuosity factor (dimensionless); ‰ ij is the Kronecker delta function (δ ij = 1 if i = j, and…”
Section: Subsurface Solute Transportmentioning
confidence: 99%
“…The first strategy uses the soil advection-dispersion equation. One-and twodimensional forms of this equation have been used for border/basin and furrow irrigation, respectively (Zerihun et al, 2005a;Ebrahimian et al, 2013a). The twodimensional approach is used to represent the soil underneath a cross-sectional furrow section.…”
Section: Subsurface Solute Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…The HYDRUS (2D/3D) model and its predecessors, such as SWMS-2D and HYDRUS-2D, have been widely used in the past to simulate water flow and/or solute transport for furrow irrigation systems (e.g., Benjamin et al 1994;Abbasi et al 2003aAbbasi et al , b, 2004Rocha et al 2006;Wöhling et al 2004aWöhling et al , b, 2006Mailhol et al 2007;Warrick et al 2007;Wöhling and Schmitz 2007;Wöhling and Mailhol 2007;Crevoisier et al 2008;Lazarovitch et al 2009;Ebrahimian et al 2012Ebrahimian et al , 2013aZerihun et al 2014). For example, Benjamin et al (1994) simulated fertilizer distribution in the soil under broadcast fertilization for conventional and alternate furrow irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, shallow wetting irrigation and shallow irrigation combined with timely fi eld drying has shown that the paddy fi eld had more suffi cient sunlight than that in fl ooding irrigation, which could increase fi nal rice yield [7][8][9]. Alternate furrow irrigation, applying water to one of two continuous furrows, has been applied mainly in arid and semi-arid regions to conserve water and to increase water productivity in agricultural lands [10][11][12]. Drip irrigation can reduce the irrigation amount without reduction in crop yield and hence increase water use effi ciency by delivering water directly to the roots of the crop and reducing evapotranspiration and percolation.…”
Section: Introductionmentioning
confidence: 99%